Research capacity building in midwifery: Case study of an Australian Graduate Midwifery Research Intern Programme - Hauck, Yvonne; Lewis, L.; Bayes, S.; Keyes, L. (Elsevier, 2015)
Background: Having the research capacity to identify problems, create new knowledge and most importantly translate this knowledge into practice is essential within health care. Midwifery, as well as other health professions in Australia, is challenged in building its research capacity to contribute evidence to inform clinical practice. Aim: The aim of this project was to evaluate an innovative Graduate Midwifery Research Intern Programme offered at a tertiary obstetric hospital in Western Australia, to determine what was working well and how the programme could be improved. Method: A case study approach was used to gain feedback from graduate midwives within a Graduate Research Intern (GRI) Programme. In addition outcomes were compiled of all projects the GRI midwives contributed to. Six GRI midwives participated in a survey comprising of four open ended questions to provide feedback about the programme. Results: Findings confirm that the GRI programme increased the graduates understanding of how research works, its capacity to define a problem, generate new knowledge and inform clinical practice. The GRI midwives' feedback suggested the programme opened their thinking to future study and gave them enhanced insight into women's experiences around childbirth. Conclusion: To grow our knowledge as a professional group, midwives must develop and promote programmes to build our pool of research capable midwives. By sharing our programme evaluation we hope to entice other clinical settings to consider the value in replicating such a programme within their context.